2007
DOI: 10.1111/j.1600-0560.2006.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis in regressing melanoma versus nonfibrosis in halo nevus upon melanocyte disappearance: Could it be related to a different cytokine microenvironment?

Abstract: Fibrogenic cytokines were more frequently expressed in melanoma than in halo nevus, irrespective of regression. At ultrastructural level, melanocytes showed a more activated status in regressing melanoma than in halo nevus, in compliance with a milieu richer in cytokines. Although the cytokine microenvironment does not completely justify the fibrotic evolution in regressing PM, the higher TNF-alpha expression in halo nevus suggests a possible role in nonfibrotic evolution of this lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 19 publications
(54 reference statements)
0
26
1
1
Order By: Relevance
“…They also activate CD8 + T cells and cause melanocyte destruction [28]. The ratio of CD4 + T cells to CD8 + T cells has been reported to vary from 1:1 to 1:3 [27,28,29]. This study, however, revealed a predominance of CD8 + T cells; CD4 + T cells were rarely observed.…”
Section: Discussioncontrasting
confidence: 49%
“…They also activate CD8 + T cells and cause melanocyte destruction [28]. The ratio of CD4 + T cells to CD8 + T cells has been reported to vary from 1:1 to 1:3 [27,28,29]. This study, however, revealed a predominance of CD8 + T cells; CD4 + T cells were rarely observed.…”
Section: Discussioncontrasting
confidence: 49%
“…The prototype of regressing melanocytic nevus is a ‘halo’ nevus which is usually unassociated with a melanoma 13 . Moretti et al 14 observed that the T‐cell infiltrate and cytokine milieu is distinct in regressed melanoma (in which melanocyte disappearance is coupled with fibrosis) when compared with regressing halo nevi (in which melanocyte disappearance elicits inconspicuous fibrosis). Areas of regressed melanoma contain a predominance of CD4‐positive T cells, while halo nevi are rich in CD8‐positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both IL-6 and TGF-β are well-known fibrotic cytokines, and numerous fibrotic skin conditions are characterized by the coexpression of these cytokines. For instance, skin surrounding regressing melanoma is highly fibrotic and displays increased expression of IL-6 and TGF-β levels, whereas the skin around halo naevi is not fibrotic and does not show elevated expression of these cytokines 80. Damage by ionizing radiation also causes fibrotic changes that appear to be linked to IL-6 and TGF-β expression (review81).…”
Section: Discussionmentioning
confidence: 99%